Industrially scalable Chitosan/Nylon-6 (CS/N) nanofiber-based reusable adsorbent for efficient removal of heavy metal from water. (20th January 2021) - Kakoria, Ashish; Sinha-Ray, Suman; Sinha-Ray, Sumit
Abstract: Industrially scalable fabrication of Chitosan (CS)/Nylon-6 (N) based nanofiber membrane was achieved using novel Solution Blowing technique with 40% Nylon-6 being replaced with Chitosan. The membrane was used as an efficient, reusable adsorbent of heavy metal (Cu 2+ ) from water encompassing a wide range of metal ion concentrations, namely- 3–100 mg/L. At pH- 4 the adsorption was most favorable, and the maximum capacity was found to be as high as 240 mg/g owing to highly available active amine (- N ¨ H 2 ) groups. At lower concentration, the adsorption profile could be matched with both Langmuir and Freundlich adsorption isotherms. However, both isotherms failed at higher concentration regime, hypothesizing possible access to sub-surface availability of active sites, which is otherwise not reported for fiber-based adsorbents as per best of knowledge of authors. Large scale (4L) demonstration with such adsorbent, with 90% metal ion removal efficiency, exhibits the potential of the membrane in practical applications. The membrane could be reused up to 8 times where the leachate can be used for metal extraction. Graphical abstract: Image 1 Highlights: Chitosan embedded Nylon-6 nanofiber-based membrane was used to remove Cu 2+ from water with Chitosan content as high as 40%. Nanofiber membranes showed efficient removal (max of 240 mg/g) within a wide range of concentrations of Cu 2+ (3-100 mg/L). Nanofiber membrane allowed adsorption at surface and sub-surface scale active sites. Such adsorbents could be reused up to 8 cycles with minimum efficiency of 50% allowing possible extraction of heavy metals.